2007
DOI: 10.1016/j.otohns.2007.04.026
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of Hep‐2 cell with multiple drug resistance induced by Taxol

Abstract: These findings may provide theoretical support for the reverse of MDR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…In a previous study, it was demonstrated that the expression of MDR1/P-gp in human laryngeal cancer tissues was associated with malignant progression and metastasis (9). Furthermore, several studies have reported that MDR1/P-gp may serve a crucial role in the regulation of MDR in laryngeal cancer cells (10,11). Zhigang et al (11) observed that the inhibition of MDR1/P-gp expression served as an effective method to reverse MDR in laryngeal cancer cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a previous study, it was demonstrated that the expression of MDR1/P-gp in human laryngeal cancer tissues was associated with malignant progression and metastasis (9). Furthermore, several studies have reported that MDR1/P-gp may serve a crucial role in the regulation of MDR in laryngeal cancer cells (10,11). Zhigang et al (11) observed that the inhibition of MDR1/P-gp expression served as an effective method to reverse MDR in laryngeal cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…It is understood that MDR1/P-gp serves a crucial role in regulating intracellular drug concentrations, consequently determining the drug sensitivity of human cells. Recently, MDR1/P-gp has been elucidated to be involved in the regulation of MDR in human laryngeal cancer cells (10,11), with the inhibition of MDR1/P-gp expression having been confirmed as an effective method to reverse MDR in such cells (11). Furthermore, previous data have demonstrated that MDR1/P-gp expression is significantly upregulated in response to hypoxia in laryngeal cancer cells (12).…”
Section: Introductionmentioning
confidence: 99%
“…The CNE, Hep-2 and FaDu cell lines from human nasopharyngeal, laryngeal and hypopharyngeal cancers, were obtained from the American Type Culture Collection (ATCC). A taxol-resistant cell line (Hep-2T) was developed by continuous exposure of Hep-2 cells to stepwise escalating concentrations of taxol for 12 months (24). All of the cell lines were cultured in Dulbecco's modified Eagle's medium (DMEM), supplemented with 10% fetal bovine serum, 100 U/ml penicillin and 100 µg/ml streptomycin at 37˚C in a humidified atmosphere composed of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The laryngeal carcinoma cells Hep-2 was gained from the American Type Culture Collection (ATCC) and multidrug-resistant cell variant Hep-2T had been prepared and characterized in our previous work (Li et al, 2007). All cell lines were maintained as monolayers in Dulbecco's modification of Eagle's medium (DMEM; Gibco Corporation, USA), supplemented with 10% fetal bovine serum (Hyclone, USA) and antibiotics (100 IU/ ml penicillin and 100 IU/ml streptomycin) at 37°C in a humidified atmosphere containing 95% air and 5% CO 2 .…”
Section: Cell Line and Culturementioning
confidence: 99%